Development and Application of an Annotation Procedure to Assess the Impact of Hearing Aid Amplification on Interpersonal Communication Behavior. (December 2018) - Meis, Markus; Krueger, Melanie; Gablenz, Petra v.; Holube, Inga; Gebhard, Maria; Latzel, Matthias; Paluch, Richard
Hearing impairment is associated with a decrease in speech intelligibility and health-related quality of life, such as social isolation and participation restriction. However, little is known about the extent to which hearing impairment and hearing aid fittings change behavior in acute communication situations as well as interrelated behavior patterns. Based on a pilot study, in which the basis for annotating communication behavior was laid, group discussions in noise were initiated with 10 participants using three different hearing-aid brands. The proposed offline annotation scheme revealed that different hearing aids were associated with changes in behavior patterns. These behavioral changes were congruent with speech recognition threshold results and also with subjective assessments. Some of the results were interpreted in terms of participation restriction and activity limitation following the framework of the International Classification of Functioning, Disability and Health. In addition to the offline annotation scheme, a procedure for instantaneous coding of eight behavior patterns was iteratively developed and used for the quick examination of lab studies with good to excellent interrater reliability values.